Histological Architecture of Gastric Epithelial Neoplasias That Showed Absent Microsurface Patterns, Visualized by Magnifying Endoscopy with Narrow-Band Imaging - Kenta Chuman; Kenshi Yao; Takao Kanemitsu; Takashi Nagahama; Masaki Miyaoka; Haruhiko Takahashi; Kentaro Imamura; Rino Hasegawa; Toshiharu Ueki; Hiroshi Tanabe; Seiji Haraoka; Akinori Iwashita (Korean Society of Gastrointestinal Endoscopy, 2021)
Background/Aims The objective of this study was to elucidate the histological structure of the absent microsurface patterns (MSPs) that were visualized by magnifying endoscopy with narrow-band imaging (M-NBI). Methods The study included consecutive gastric epithelial neoplasias for which M-NBI findings and histological findings could be compared on a one-to-one basis. The lesions were classified as absent MSPs and present MSPs based on the findings obtained using M-NBI. Of the histopathological findings for each lesion that corresponded to M-NBI findings, crypt opening densities, crypt lengths, crypt opening diameters, intercrypt distances, and crypt angles were measured and compared. Results Thirty-six lesions were included in the analysis; of these, 17 lesions exhibited absent MSP and 19 lesions exhibited present MSP. Comparing the histological measurements for absent MSPs vs. present MSPs, median crypt opening density was 0.9 crypt openings/mm vs. 4.8 crypt openings/mm (p<0.001), respectively. The median crypt length, median crypt opening diameter, median intercrypt distance, and median crypt angle were 80.0 μm vs. 160 μm (p<0.001), 40.0 μm vs. 44.2 μm (p=0.09), 572.5 μm vs. 166.7 μm (p<0.001), and 21.6 degrees vs. 15.5 degrees (p<0.001), respectively. Conclusions Histological findings showed that lesions exhibiting absent MSPs had lower crypt opening density, shorter crypt length, greater intercrypt distance, and larger crypt angle.